Structure and inhibition of Cryptococcus neoformans sterylglucosidase to develop antifungal agents - Nivea Pereira de Sa (Nature Portfolio, 2021)
Sterylglucosidase 1 (Sgl1) is a virulence factor in Cryptococcus neoformans that modulates fungal pathogenesis and host response. Here, the authors characterize Sgl1 structurally, identify Sgl1 inhibitors, and demonstrate Sgl1 inhibition has efficacy in mouse models of infection.